Self-regulation and social welfare: The political economy of corporate environmentalism - John W. Maxwell; Thomas Peyton Lyon; Steven Curtis Hackett (Fondazione Eni Enrico Mattei (FEEM), 1998)
We extend the economic theory of regulation to allow for strategic self-regulation that preempts political action. When political "entry" is costly for consumer, firms can deter it through voluntary restraints. Unlike standard entry models, deterrence is achieved by over-investing to raise the rival's welfare in the event of entry. Empirical evidence on releases of toxic chemicals shows that an increased threat of regulation (as proxied by increased membership in conservation groups) indeed induces firms to reduce toxic releases. We establish conditions under which self-regulation, if it occurs, is a Pareto improvement once costs of influencing policy are included.
Keywords: D72; K32; L51; Q28; 330; Regulation; Environment; Self-regulation; Political Economy; Umweltmanagement; Selbstverpflichtung; Regulierungstheorie; Wohlfahrtstheorie; Neue politische Ökonomie; Theorie